An appraisal of the proviso to S 16 (1)(A) of Sale Of Goods Act 1957 - Haniff Ahamat (Fakulti Undang - Undang, 2001)

(untitled)
Fitness for particular purpose is one of the exceptions to the common law principle of caveat emptor. It allows buyers to rely on the exception that is an implied condition, the breach of which entitles them to repudiate a contract of sale of goods. However the exception is subject to a condition – the goods should not be bought under patent or trade name. This condition can be found in the proviso to section 16(1)(a) of the Sale of Goods Act 1957. As such this article attempts to explain the basic principles underlying the proviso in light of the latest local cases like Union Alloy, Sunrise Bhd and Medicon Plastic. The finding is that the proviso is arguably applicable only to simple consumer goods while highly complicated goods like machinery in factories are outside its purview. The finding is that the proviso is arguably applicable only to simple consumer goods while highly complicated goods like machinery in factories are outside its purview. But the law in England post 1979 amendment has significantly changed with the equivalent proviso being scrapped. Thus the article suggests the Malaysia law to follow the same trend to the benefit of the consumers and public at large